IMPACT OF THE RIGHT VENTRICLE DYSFUNCTION ON CHRONIC HEART FAILURE PRESENTATION IN PATIENTS WITH HYPERTROPHIC CARDIOMYOPATHY - N. G. Poteshkina; A. E. Demkina; N. S. Krylova; E. A. Kovalenskaya; F. M. Khashieva (Российский кардиологический журнал)
Aim. To assess the function of the right ventricle (RV), its influence on clinical and instrumental presentation of chronic heart failure (CHF) in patients with hypertrophic cardiomyopathy (HCMP).Material and methods. Totally, 55 patients with HCMP included, males 17 (34%), mean age — 57,0±15,2 y. All patients were taking bisoprolol 5,7±1,2 mg. The study included assessment of clinical status of patients with Minnessota score of life quality in CHF, SQCA, brain natriuretic peptide (BNP) measurement in plasma, echoCG. With the aim to deeper investigate on cardiac function we asessed Tei index of the left ventricle (LV) and RV. As the result of all studies in HCMP there was increase of Tei of LV. Increase of RV Tei was found in 35 patients (63,6%). By Tei RV value, patients were selected to 2 groups: 1 group (n=35) — those with Tei RV higher than normal — ≥0,32 (0,58±0,2), 2 group (n=20) — with Tei RV <0,32 (0,23±0,09).Results. Patients from group 1 had higher clinical and laboratory markers of CHF: FC CHF by NYHA (p=0,008), summ by SQCA (p=0,03), BNP level in plasma 200 (p=0,01). In 1st group patients there was higher E/A (p=0,04), transmitral flow, lower regional systolic velocity on septal part of mitral annulus (MVFA) (p=0,04), free wall of tricuspid valve fibrous annulus (TVFA) (p=0,01), longer the time of isovolumetric relaxation on lateral (p=0,04) and posterior (p=0,03) regions of MVFA. There was negative correlation of Tei RV index and peak A (p=0,0007) and postitve — with E/A of transmitral flow (p=0,01). There was correlation of FC CHF by NYHA and s’ of free wall of TVFA (p=0,04); positive association of Tei RV and FC level of CHF by NYHA, BNP (p=0,01). There was negative association of BNP and systolic function of RV: s’ TVFA (p=0,01), s’ of basal part of RV free wall (p=0,002), s’ of median part of RV free wall (p=0,02).Conclusion. Presence of RV dysfunction by Tei index was found in 63,5% of patients with HCMP. RV dysfunction in HCMP is due to severely disordered diastolic dysfunction of LV, is followed by progression of CHF — increase of FC CHF, SQCA points summ, BNP level and decrease of segmental longitudinal function of myocardium by TDI.